Evidence of SARS-CoV-2-Specific Memory B Cells Six Months After Vaccination With the BNT162b2 mRNA Vaccine - Ciabattini, Annalisa; Pastore, Gabiria; Fiorino, Fabio; Polvere, Jacopo; Lucchesi, Simone; Pettini, Elena; Auddino, Stefano; Rancan, Ilaria; Durante, Miriam; Miscia, Michele; Rossetti, Barbara; Fabbiani, Massimiliano; et al. (Frontiers in Immunology, 2021)
SARS-CoV-2 mRNA vaccines have demonstrated high efficacy and immunogenicity, but limited information is currently available on memory B cell generation and long-term persistence. Here, we investigated Spike-specific memory B cells and humoral responses in 145 subjects, up to six months after the BNT162b2 vaccine (Comirnaty) administration. Spike-specific antibody titers peaked 7 days after the second dose and significant titers and neutralizing activity were still observed after six months, despite a progressive decline over time. Concomitant to antibody reduction, Spike-specific memory B cells, mostly IgG class-switched, increased in blood of vaccinees and persisted six months after vaccination. Following in vitro restimulation, circulating memory B cells reactivated and produced Spike-specific antibodies. A high frequency of Spike-specific IgG+ plasmablasts, identified by computational analysis 7 days after boost, positively correlated with the generation of IgG+ memory B cells at six months. These data demonstrate that mRNA BNT162b2 vaccine elicits strong B cell immunity with Spike-specific memory B cells that still persist six months after vaccination, playing a crucial role for rapid response to SARS-CoV-2 virus encounter.